Real-Time Defect Detection and Carbon Footprint Visualization in Green Construction Using Mobile Augmented Reality and Building Information Modeling - Liao, Yi; Luo, Huan (International Journal of Interactive Mobile Technologies (iJIM), 2025)
The integration of mobile augmented reality (AR) technology with building information modeling (BIM) has introduced novel solutions for construction management, particularly in real-time defect detection and carbon footprint monitoring. AR technology enables the real-time provision of three-dimensional visual information at construction sites, which, when combined with BIM, facilitates accurate defect identification and feedback. Additionally, BIM provides a scientific basis for planning carbon emission pathways in construction projects. However, existing defect detection and carbon footprint management systems face challenges such as limited accuracy and insufficient real-time capabilities. Current study on green construction primarily focuses on defect detection and carbon footprint calculations, yet most approaches continue to rely on traditional two-dimensional drawings or manual inspection, which fail to meet the real-time demands of construction sites. The absence of an integrated solution leveraging both AR and BIM technologies has constrained their practical application in construction. To address these limitations, this study proposes a real-time defect detection and carbon footprint visualization and path planning system for green construction, based on mobile AR technology and BIM. The system employs AR-based stereo matching for real-time defect identification and utilizes BIM for carbon footprint visualization path planning. This study aims to provide an efficient and accurate approach to defect detection while enhancing the environmental protection level during the construction process through effective carbon footprint management.